On the effect of the node and building orientation on the fatigue behavior of L‐PBF Ti6Al4V lattice structure sub‐unital elements. Issue 6 (3rd July 2021) - Murchio, Simone; Dallago, Michele; Rigatti, Andrea; Luchin, Valerio; Berto, Filippo.; Maniglio, Devid; Benedetti, Matteo
Abstract: Despite the great potential of additively manufactured (AM) metallic lattice materials, a comprehensive understanding of their mechanical behavior, particularly fatigue, has yet to be achieved. The role of the sub‐unital lattice elements, that is, the struts and the nodes (or strut junctions), is rarely explored, even though it is well known that fatigue is a local phenomenon, determined by the small features of a structure (defects and local geometrical discontinuities). In this work, the mechanical behavior of nodes and struts has been investigated by designing laser powder bed fusion (L‐PBF) Ti6Al4V single strut specimens, with a node placed in the central part of the gauge length. The specimens were manufactured according to four different building orientations, namely, 90°, 45°, 15°, and 0° to the build plane. The influence of the fillet radius at the node and of the printing direction on the fatigue strength has been examined.